Power and violence: the visual discourse of the Christopher Columbus monument (and the indigenous woman) - Ayala Del Río Cépeda, David (2022)
The management of cultural heritage becomes a contested field in which the collective imaginaries play a central role. Accordingly, different elements composing our urban landscape are being criticized and within this critique the case of the Christopher Columbus monument will be addressed, by breaking down the patriarchal and colonial symbolic elements of its composition. To this effect, an historical analysis of the social and cultural processes leading to the normalization of these monuments throughout the development of the republic, and the response in the collective consciousness that has led to different actions and critical initiatives. The article thus aims to open a reflective debate on the development of our republic in the face of the bicentennial and to draw attention on the necessary critical management of our public spaces.